A Population-Based Cross-Sectional Study of the Association between Liver Enzymes and Lipid Levels - Subrata Deb; Prasanth Puthanveetil; Prashant Sakharkar (International Journal of Hepatology)
Background. To examine the association between low-density lipoprotein (LDL) and high-density lipoprotein (HDL) levels and liver enzyme functions. Methods. The National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2012 was used to examine the association between liver enzymes and lipid levels amongst adults in the United States. Results. Sixteen percent adults had ALT > 40 U/L, 11% had AST > 40 U/L, and 96% had ALP > 120 U/L. Age, gender, and race/ethnicity showed significant association with LDL, HDL, and triglycerides levels. LDL greater than borderline high was associated with little over two times higher odds of elevated ALT (OR: 2.33, 95% CI: 2.17, 2.53, p≤0.001) and AST (OR: 2.79, 95% CI: 2.55, 3.06, p≤0.001). High HDL was associated with 50% higher odds for elevated ALT (OR: 1.51, 95% CI: 1.39, 1.64, p≤0.001) and over two-and-half fold elevated AST (OR: 2.77, 95% CI: 2.47, 3.11, p≤0.001). LDL-C, HDL-C, and triglycerides were found to be good predictor of elevated ALT, AST, and ALP levels. Similarly, old age and female gender were significant predictor of elevated ALT and AST (p≤0.001). Conclusions. Underlying hepatic pathophysiology from dyslipidemia deserves further exploration due to its potential effects on hepatic drug metabolism/detoxification.